Study the Cognitive Independence and the Mental Motivation in the Administrative and Technical Staff in The Department of Sports Talent - Abd, Mohannad Taleb (International Journal of Psychosocial Rehabilitation, 2020)
identify the relationship between cognitive independence and mental motivation for the administrators and technicians of the specialized schools. The Department of Sports Talent in Baghdad. The importance of research in dealing with a new topic not studied in the Iraqi environment.The research sample consisted of (119) individuals The research problem will determine by the level of cognitive independence and mental motivation of the technicians and administrators of the Department of Sports Talent in the specialized schools in Baghdad. To achieve the goal of the research, the researcher used the test of cognitive independence and the Ismailia measure of mental motivation. Between cognitive independence and psychological motivation‘The Research Problem What is the level of cognitive independence of technicians and administrators of the Department of Sports Talent in the specialized schools in Baghdad?The research aims to know the level of cognitive independence and mental motivation among technicians and administrators of the specialized schools in the Department of Mathematical Talent, and the relationship between them. Statistical treatments have been made for the data obtained from the two research tools to achieve the search results, and the researcher will display the results that he reached through the application of the research tools as well as an explanation and analyze the results.